Factors that influence the presence of carotid atherosclerosis in people living at high altitudes - Diaz-Lazo, Anibal (2025)
Objective: The aim was identify the factors associated with the development of carotid atherosclerosis in high altitude inhabitants. Material and Methods: Evaluation with carotid Doppler ultrasound was carried out on 144 people over 40 years of age from and native to Huancayo, Peru, located between 3000 and 4000 meters above sea level (m.a.s.l), sociodemographic data and their results from the studies were recorded. laboratory. Factors affecting carotid atherosclerosis were compared using logistic regression analysis. Results: Of the total participants, the average age was 59 years, 73 people (50.7%) were male, the average body mass index was 27. The morbidities identified were arterial hypertension (HTA) (OR 2.63; 95% CI: 1.81-5.89; p=0.018), diabetes mellitus (OR 1.74; 95% CI: 1.04-3.48; p=0.041), and dyslipidemia (OR 1.87; 95% CI: 1.09-3.63; p=0.037). Duration of HTA for 5 years and over increases the probability of developing atherosclerosis by 70% (95% CI: 0.61-0.87). Conclusions: The factors associated with the formation of carotid atherosclerosis in high altitude inhabitants were HBP, diabetes mellitus, dyslipidemia and age over 55 years. Early diagnosis and control of HTN is recommended to reduce the risk of atherosclerosis.